Deep learning for studying urban water bodies´ spatio-temporal transformation: a study of Chittagong City, Bangladesh - Enan, Muhammad Esmat (2021)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies